Pengaruh Pijat Bayi terhadap Peningkatan Berat Badan - Fitriyanti, Yuyuk Eva; Arsyard, Gusman; Sumiaty, Sumiaty (Poltekkes Kemenkes Palu, 2019)
Indicator of child growth is weight. At the age of 1-3 months is a period of rapid growth, so it is necessary to maintain a baby's weight according to age. In the Sangurara Community Health Center work area, the second highest case of weight (BGM) was recorded with 30 babies. Touch therapy or massage is one technique that combines the physical benefits of human touch with emotional benefits such as bounding and increasing weight.The purpose of this study was to determine the effect of infant massage on weight gain in infants aged 1-3 months in the work area of the Sangurara Health Center in Palu City. Palu City. This type of research is a Quasi-experimental design with pretest and Posttest control group design. The sample in this study were 30 months old infants as many as 30 infants with sampling technique consecutive sampling. Data analysis using test Chi-square with a confidence level of 95% (? = 0.05). The results showed that babies who were massaged had more weight gain, which was 24.07%, while babies who were not massaged had a weight gain of 18.28%. This is evidenced by the value of p value: 0.03 (p.value?0.05). In conclusion, there is the effect of Baby Massage on Increased Body Weight. Suggestions for researchers for health workers to socialize and suggest baby massage to reduce the case of BGM weight (Under the Red Line) in infants.